TRANSFORMASI PEMBELAJARAN MATEMATIKA MATERI BILANGAN CACAH MELALUI WORDWALL PADA SISWA KELAS III - Khusmiati Dewi; Zahrani Susilo, Claudya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The main focus of this study was on the effectiveness of the interactive media Wordwall in optimizing the learning of integer multiplication for third-grade elementary school students. Using a quantitative approach and a one-group pretest-posttest design, the study involved 28 students as the main sample. The background of this study stemmed from the situation of students with difficulties in mastering basic mathematical concepts and low motivation towards the subject. The research instruments consisted of multiple-choice and essay tests administered during the pretest before learning using Wordwall and the posttest after learning. The normality test results showed that the data were normally distributed and therefore suitable for parametric analysis. The paired sample t-test showed an increase in the average score from 57,11 to 83,93 with a difference of 26,82 points and a very large effect size, so that Wordwall was declared effective in improving learning outcomes in mathematics on the subject of multiplication of whole numbers.